Критика "новейших" буржуазных педагогических теорий - Бернштейн Михаил Семенович ([Серия 2, 1959)
Экземпляры: КХ (20120913) / Инвентарный номер: 095951 / Цена: 0.60 / Сис.шифр: 37Б / Авт.знак: Б 51 / ГРНТИ: 14 / ББК: 74